Immunomodulatory Effects of Food Additives - Hamid Y Dar; Shivani Chaturvedi; Karishma Srivastava; Zaffar Azam; Rajaneesh Anupam; Rajesh K Mondal; Geetanjali B Tomar; Ashish K Singh; Pradyumna K Mishra; Rupesh K Srivastava (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
Food items that are unprocessed and do not contain preservatives, artificial colours, chemicals, fillers, artificial flavours etc are called as Natural foods. Natural foods are the best source of nutrition and health. Substances added to natural food to preserve fl avour and increase their life are named as food additives. When food is to be stored for a long period, additives and preservatives are required to maintain the quality and fl avour of the food items. The additives and preservatives prevent bacterial and fungal growth due to excess water in the foods [1]. Additives are defi ned by the United States Food and Drug Administration (FDA) as "any substance, the intended use of which results or may  reasonably be expected to result, directly or indirectly, in its becoming a component or otherwise affecting the characteristics of any food." Direct additives are those that are intentionally added to foods for a specifi c purpose. Indirect additives are those to which the food is exposed during processing, packaging, or storing. Preservatives are additives that inhibit the growth of bacteria, yeasts, and moulds in foods [2].